2021
DOI: 10.3390/biology10030242
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 Single Nucleotide Polymorphism Prevalence and Association with Liver Disease in a Diverse Cohort of Persons Living with HIV

Abstract: In persons living with HIV (PLWH), there are multiple sources of liver injury. Gene polymorphisms of PNPLA3 (patatin-like phospholipase domain-containing protein 3) have been identified as an important cofactor for increased disease severity in both alcoholic and non-alcoholic steatohepatitis (NASH). We utilized a well-characterized cohort of ethnically and racially diverse patients with HIV to define the prevalence of PNPLA3 SNPs (single nucleotide polymorphism) (rs738409), and to determine the relationship t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Studies analyzing the association between PNPLA3 and NAFLD in PLWHIV are more recent and report varying results ( Sherman et al, 2021 ) ( Price et al, 2014 ) ( Dold et al, 2017 ). It is important to note that the diagnostic methods used to identify NAFLD included CAP, liver ultrasound, and magnetic resonance, thus explaining in part this variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies analyzing the association between PNPLA3 and NAFLD in PLWHIV are more recent and report varying results ( Sherman et al, 2021 ) ( Price et al, 2014 ) ( Dold et al, 2017 ). It is important to note that the diagnostic methods used to identify NAFLD included CAP, liver ultrasound, and magnetic resonance, thus explaining in part this variability.…”
Section: Discussionmentioning
confidence: 99%
“…Such variable results could also be explained by racial and ethnic differences between the populations in the various studies. It is well known that problem alleles are not very frequent in Black individuals, whereas Latin Americans more frequently have the G allele ( Sherman et al, 2021 ). The percentages found for the different allelic variants of each gene in our study are within the expected frequencies in study populations according to race and ethnicity, thus explaining why we did not find an AA homozygote in TM6SF2 (the expected frequency is 0.08 in Europeans and 0.03 in Latin Americans) ( Trépo and Valenti, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors of developing NAFLD include features of the metabolic syndrome, including type 2 diabetes mellitus (T2DM) and insulin resistance, obesity, increased waist circumference, hypertension, and dyslipidemia (11). In PWH, additional risk factors include immune activation, adipose tissue dysfunction, ART associated with mitochondrial dysfunction, or genetic polymorphism (12,13). The spectrum of NAFLD can range from simple steatosis to steatohepatitis leading to fibrosis and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the previous series including adults living with HIV [5], we also found a significant group of lean patients presenting with NAFLD, suggesting again that body mass index and metabolic risk factors contribute to NAFLD pathogenesis but do not fully explain NAFLD among PWH. Genetic polymorphisms, among other factors, have been suggested to determine NAFLD among PWH [6,7]. As mentioned by Sabatini et al [1] intrauterine growth restriction has been identified as a key factor for future obesity in the general population, and it could definitely be playing a role here, as premature birth and low weight for height have been described among children born to HIV-infected mothers [8].…”
mentioning
confidence: 99%